A ruptured vulvar labial artery pseudoaneurysm causes a secondary postpartum hemorrhage: A case report - Marie-Claire Leaf; Luke Schmidt; Tasha Serna-Gallegos; Felicia Lane (Elsevier, 2020)
Background: Postpartum hemorrhage is the most common cause of maternal morbidity in the United States. However, secondary postpartum hemorrhage is rare and includes pseudoaneurysms, which represent only 3.3% of all cases of secondary postpartum hemorrhage. Vulvar labial artery pseudoaneurysm had never been reported in the literature. Case: This is a case of ruptured vulvar labial pseudoaneurysm leading to secondary postpartum hemorrhage. Computerized tomography angiography showed it to be located in a distal branch of the vulvar labial artery. This location is unique, although there are reported cases of pseudoaneurysms in the uterine artery. The patient was successfully treated with arterial embolization. Conclusion: Recognition of a ruptured pseudoaneurysm as the cause of postpartum hemorrhage allows for its proper management by arterial embolization. Keywords: Pseudoaneurysm, Postpartum hemorrhage, Obstetric care, Case report